Edukasi Stimulasi Janin Secara Audiovisual Mempengaruhi Tingkat Pengetahuan Ibu Hamil - Intan Nuraini Haka; Sri Setiasih; Triana Sri Hardjanti (Midwifery Care Journal, 2022)
The brain is an important organ in determining a child's intelligence. The brain is formed in the fetus from the age of 8-14 weeks. Children who get a lot of stimulation since in the womb will develop faster than those who get less or no stimulation. Of course, along with balance nutrition. This research was conducted at the Independent Midwife Practice (PBM) of Nurhayati Karang Anyar, South Lampung, with a preliminary study that out of 6 pregnant women, 5 pregnant women often gave touch, they just did not understand that it was stimulation, and 1 pregnant woman did not know how to stimulate fetus, but shows a curious attitude. The purpose of this study was to determine the effect of education through audiovisual media on the level of knowledge of pregnant women about fetal stimulation. This research method is descriptive quantitative with a quasi-experimental design with a pre-post test group approach. The sample of this study was 73 pregnant women, with the results of the study there was an increase in knowledge of pregnant women with an average score before education of 17.58 and an average value after 19.98, and there was a significant effect on education through audiovisual media on mother's knowledge. pregnant about fetal stimulation